Better Identification of Cognitive Decline With Interleukin-2 Than With Amyloid and Tau Protein Biomarkers in Amnestic Mild Cognitive Impairment - Liang, Chih-Sung; Tsai, Chia-Lin; Lin, Guan-Yu; Lee, Jiunn-Tay; Lin, Yu-Kai; Chu, Che-Sheng; Sung, Yueh-Feng; Tsai, Chia-Kuang; Yeh, Ta-Chuan; Chu, Hsuan-Te; Su, Ming-Wei; Yang, Fu-Chi (Frontiers in Aging Neuroscience, 2021)
The rate of cognitive decline among patients with amnestic mild cognitive impairment (aMCI) varies, and it is thus crucial to accurately predict the probability of cognitive deterioration in patients with MCI. We compared the potential of cytokines with amyloid beta (Aβ) and tau biomarkers for predicting cognitive decline in patients with aMCI or Alzheimer’s disease (AD). All participants (controls, aMCI, and AD patients) underwent plasma biomarker examinations for Aβ1-40, Aβ1-42, total tau (t-tau), tau phosphorylated at threonine 181 [p-Tau181]), and 29 cytokines and baseline cognitive tests, including Mini-Mental State Examination (MMSE). The correlation between biomarker levels and annual MMSE change during the follow-up was examined. Receiver operating characteristic (ROC) curve analysis was performed to determine whether the statistically significant plasma biomarkers could identify cognitive decline. Higher baseline levels of IL-2, sCD40L, and VEGF were associated with a lower annual cognitive decline in the aMCI group, and higher baseline levels of IFNγ, IL-5, IL-17A, IL-25, FGF, GM-CSF, and VEGF were associated with a rapid annual cognitive decline in the AD group. IL-2 had a high discriminatory capacity for identifying cognitive decline, with an area under curve (AUC) of 85.7% in the aMCI group, and the AUC was slightly increased when combining IL-2 with Aβ or tau biomarkers. However, none of the biomarkers had a satisfactory discriminatory capacity in the AD group. IL-2 may have a better discriminatory capacity for identifying cognitive decline than Aβ and tau biomarkers in patients with aMCI.